Poems, 1957-1967 - Dickey, James (Wesleyan poetry., 2011)
Specifically, Poems 1957-1967 contains 15 of the 24 poems that were included in his first book, Into the Stone (1960); 25 of the 36 that made up Drowning With Others (1962); 22 of the 24 in Helmets (1964); the entire 22 in the National Book Award winner Buckdancer's Choice (1965); and, under the titles Sermon and Falling, the exciting new poems mentioned above. Seldom can the word "great" be used of the work of a contemporary in any art. But surely it applies to the poems of James Dickey.